DIAGNOSIS OF STUDENTS’ ERRORS IN FINDING AREAS BY INTEGRATION - Nurhasanah, Nurhasanah; Dollo, Asdar (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to diagnose students’ errors in finding the area using integration. Errors can be seen from the student completion steps that are not correct. This type of research is qualitative research. The applied instruments were diagnostic tests and interview guidelines. The subjects consisted of Universitas Muhammadiyah Parepare students from Mathematics Education Study Program. Then, the researchers selected three subjects from 23 subjects that committed various errors. The results showed that the errors were: (1) Conceptual error, (a) substitution errors for the lower bound and upper bound, (b) misunderstanding in drawing the graph of a function. (2) Procedural errors dealing with incorrect calculation operation. (3) Final solution errors dealing with incapability to find the accurate answers based on the questions. Therefore, it is necessary to diagnose errors made by students using integration to calculate the area so that for lecturers, it becomes a reference to minimize errors made by students and find solutions for the mistakes made.